An Overview of Dental Anxiety and the Non-Pharmacological Management of Dental Anxiety. Issue 4 (May 2018) - Hare, Jennifer; Bruj-Milasan, Geanina; Newton, Tim
In this article we will seek to provide an overview of dental anxiety and fear, including its most extreme manifestation, dental phobia. We will explore the prevalence of different levels of dental anxiety and outline some broad principles for the management of dental anxiety based on an approach which suggests that management should be proportionate to the level of anxiety.